Influencia de la mineralogía de arcillas, textura y contenido de carbono orgánico sobre el índice de friabilidad de suelos cultivados con caña de azúcar - Avila, Edgar Alvaro (2016)
Influence of clay mineralogy, texture, and organic carbon content on the friability index of soils cultivated with sugar cane. Friability is a physical property that is essential to the mechanical management of soil and its behavior is associated with the nature of other edaphic properties; therefore, it must be investigated with integrated studies using different mineralogical, physical, and chemical properties. The effect of the predominance of the clay mineral types 1:1 and 2:1, the texture, and the organic carbon (CO) content, on the friability index (IF) of soils cultivated with sugar cane were evaluated. The IF was determined with the coefficient of variation method, using the lower limit of the confidence interval (IFi) as reference. A total of 7280 aggregates from the Ap and A1 horizons were used, taken from 18 farms located in the Valle Geográfico of the Cauca River region, Colombia. The mineralogy of the clay fraction was determined with X-ray diffraction, the granulometric distribution by the pipette method, and the CO content by the Walkley & Black method. The statistical analysis was conducted from a descriptive and inferential focus, univariate and multivariate. No significant effect from the predominance of clays 1:1 and 2:1 on the IFi response variable was found; however,higher IFi values were observed in the descriptive approach in the soils with a predominance of clays 1:1. There was no significant effect attributable to the total silt and clay fractions (FaT and FLT) on the IFi of the soils; rather, the total sand fraction (FAT) and the CO content showed highly significant effects on the IFi, with higher IFi values in the soils with higher CO contents and lower FAT contents.